Site‐Selective Unnatural Amino Acid Incorporation at Single or Multiple Positions to Control Sugar‐Protein Connectivity in Glycoconjugate Vaccine Candidates. Issue 15 (9th February 2023) - Violo, Typhaine; Lambert, Annie; Pillot, Aline; Fanuel, Mathieu; Mac‐Béar, Jessica; Broussard, Cédric; Grandjean, Cyrille; Camberlein, Emilie
Abstract: In cellulo site‐specific unnatural amino acid incorporation based on amber stop codon reassignment is a powerful tool to modify proteins at defined positions. This technique is herein applied to the selective functionalization of the Pneumococcal surface adhesin A protein at three distinct positions. N ϵ ‐propargyloxycarbonyl‐l ‐lysine residues were incorporated and their alkyne groups reacted using click‐chemistry with a synthetic azido‐functionalized tetrasaccharide representative of one repeat unit of the Streptococcus pneumoniae serotype 14 capsular polysaccharide. Anti‐PsaA antibody response induced in mice by the trivalent glycoconjugate was determined in comparison with corresponding monovalent and randomly functionalized conjugates. Our results suggest that controlled was superior to random conjugation for preserving antigenicity. In definitive, the reported strategy offers a unique opportunity to study the impact of carbohydrate antigen‐carrier protein connectivity on immunogenicity. Abstract : Antigen‐carrier connectivity, if controlled, can help improving immunological response to glycoconjugate vaccines. In this work, it is shown that a site‐selectively triple conjugated vaccine candidate against Streptococcus pneumoniae presents a better antigenicity than its randomly conjugated counterpart.